Solid resin for UV crosslinking based additive manufacturing - Muhammad Abraar Parandya (Nanyang Technological University, 2024)
This study investigated the integration of ultraviolet (UV) curing into a modified fused deposition modelling (FDM) printer for resin-based filaments. We used solid resin as the material for UV crosslinking.